LABOUR MARKET IN SERBIA - AN OPPORTUNITY OR LIMITATION OF ECONOMIC GROWTH - Tesić, Aleksandra; Ilić, Vladimir; Tanja Djelić, Anastazija (Economics of Agriculture, 2015)
This raises the question of why some countries based their economic power to human resources, the knowledge economy and large investments in science, while others see their citizens primarily as a social category which requires the cost of education, medical treatment, social protection, salaries and pensions? The answer lies in the concept of social development, that is, whether investing in people is considered as an investment or cost. The Companys investment in human resources, education and science, the investments are those companies that are leaders of development and their economies recorded the highest growth rates in recent history. Opposite them are the companies that have not yet recognized the importance of education and investment in people as the most important resource and a factor of development. Such companies are on the margins of development, marginalized and occupied "internal" problems, unaware that standing in the village, in the context of economic growth, the reverse. Serbia at this moment belongs, unfortunately, this second group of countries that do not understand the full meaning and signifcance of human potential. Under certain conditions, it is possible to reverse the existing concept and establish an open and developed labor market that will be the engine of development and a key factor of economic growth in Serbia.